Remoção de nitrogênio via processo de desamonificação utilizando-se diferentes configurações de reatores - Chini, Angélica (2015)
Nitrogen is an essential nutrient for the survival of living organisms, and although abundant as a gas (N₂), it is largely inaccessible in this form to most beings. Nitrogen only becomes accessible when converted into, for example, ammonia, nitrite and nitrate. These substances can be found in high concentrations in effluents, such as swine wastewater, generating a high concentration of nutrients, which may cause damage to the environment and to public health. Biological processes are widely used to remove high nutrients loads. In this context, anammox, partial nitritation (PN) and their combination, as deammonification, are being studied for nitrogen removal. The deammonification consists in ammonia oxidation by PN and that generates substrate to anammox activity; therefore, it must have partial nitrification control to prevent nitrite accumulation. The nitrite concentration in the reactor can inhibit the anammox process, which can be controlled with different strategies, such as aeration and reactor configuration. Considering this, the present study aimed to evaluate two reactors configurations suspended and expanded sludge, for reactor configuration evaluation on deammonification process. For this, two up flow reactors were used with intermittent feeding and aeration at 30 min cycles (15 min on/ 15 min off), one with suspended and the other with expanded bed. These possess working volume of 1 L, 55 g (w/v) of biofilm plastic carrier, the temperature was maintained at 25 °C, HRT 9 h, circulation input flow rate of 2.70 L.d⁻¹ and recirculation flow rate was 2.5 times the input and it was fed with synthetic medium. It was possible to establish deammonification process in the two reactors and the experiments were carried out: phase I and III were unstable (air flow rate of 30 mL.min⁻¹.L⁻¹) and phase II was stable (air flow rate of 20 mL.min⁻¹.L⁻¹). Thus, in the tested process conditions, it was inferred that the ideal air flow rate was of 20 mL.min⁻¹.L⁻¹. The expanded biomass reactor configuration achieved better nitrogen removal efficiencies, being 1.23 more efficient than suspended bed, thus being considered the best option for the process under study. In the anammox and nitrifying quantification, there were no significant changes in the suspended bed reactor, only nitrifying growth in phase III. For the expanded bed reactor, anammox bacteria increased in phase II. The results showed that the expanded bed reactor presented a performance 23.06% more efficient than the suspended bed reactor.